The Influence of Employee Engagement and The Use of Digital Social Media on Professional Competence Through Employee Motivation in The Government of North Jakarta Administrative City, Dki Jakarta Province - Ade Arqam Hidayat; Ahmad Hidayat; Tuswoyo Tuswoyo (Dinasti International Journal of Education Management And Social Science, 2025)
The Background of this Study is the lack of professional competence of employee in society development activity in North Jakarta region which implies to the delay of society development, since it is highly determined by people’s participation in various sectors of development. The Purpose of this Study is to analyze and evaluate the Influence of Employee Engagement and Digital Social Media Use toward Professional Competence through Motivation of Government Employees in North Jakarta Administrative City, Jakarta Capital Special Region Province. The method of this study is quantitative research with Partial Least Square (PLS) approach with Structural Equation Modelling (SEM). In this study, the population is 513 employees in Government Office of North Jakarta Administrative City of Jakarta Capital Special Region Province along with 85 samples through Simple random sampling. The Result of the Study is that the Employee engagement influences the Professional Competence in directly positive and significant way with coefficient value of = 0,107 or (10,7 % ) and Employee Engagement influences the Professional Competence in directly positive and significant way through Work Motivation with coefficient value of = 0,345 or (34,5 %. The use of Digital Social Media influences the Professional Competence in positive and significant way with coefficient value of = 0,106 or (10,6 %) and the Use of Digital Social Media influences the Professional Competence in directly positive and significant way through Work Motivation with coefficient value of = 0,270 or (27%), Motivation has a positive and significant effect on Professional Competence with coefficient value of = 0,708 or (70, 8 %). Employee engagement influences the Work Motivation in directly positive and significant way with coefficient value of = 0,488 or ( 48,8 % ). The use of Digital Social Media influences the Work Motivation in directly positive and significant way with coefficient value of = 0,381 or ( 38,1 % ). Analysis Result of the data shows that value = R-square adjusted = 0,772. Which indicates that the variation of variable changes of Professional Competence (Y) may be explained by Employee engagement, the Use of Digital Social Media, and Motivation is for 0,722 or (77,2 %). As for the rest = 22,8 % is explained by another factor.